The Chinese Parkinson's Disease Registry (CPDR): Study Design and Baseline Patient Characteristics. Issue 7 (3rd May 2022) - Zhou, Xiaoxia; Liu, Zhenhua; Zhou, Xiaoting; Xiang, Yaqin; Zhou, Zhou; Zhao, Yuwen; Pan, Hongxu; Xu, Qian; Chen, Yase; Sun, Qiying; Wu, Xinyin; Tan, Hongzhuan; et al.
Abstract: Background: There is a lack of large multicenter Parkinson's disease (PD) cohort studies and limited data on the natural history of PD in China. Objectives: The objective of this study was to launch the Chinese Parkinson's Disease Registry (CPDR) and to report its protocol, cross‐sectional baseline data, and prospects for a comprehensive observational, longitudinal, multicenter study. Methods: The CPDR recruited PD patients from 19 clinical sites across China between January 2018 and December 2020. Clinical data were collected prospectively using at least 17 core assessment scales. Patients were followed up for clinical outcomes through face‐to‐face interviews biennially. Results: We launched the CPDR in China based on the Parkinson's Disease & Movement Disorders Multicenter Database and Collaborative Network (PD‐MDCNC). A total of 3148 PD patients were enrolled comprising 1623 men (51.6%) and 1525 women (48.4%). The proportions of early‐onset PD (EOPD, age at onset ≤50 years) and late‐onset PD (LOPD) were 897 (28.5%) and 2251 (71.5%), respectively. Stratification by age at onset showed that EOPD manifested milder motor and nonmotor phenotypes and was related to increased probability of dyskinesia. Comparison across genders suggested a slightly older average age at PD onset, milder motor symptoms, and a higher rate of developing levodopa‐induced dyskinesias in women. Conclusions: The CPDR is one of the largest multicenter, observational, longitudinal, and natural history studies of PD in China. It offers an opportunity to expand the understanding of clinical features, genetic, imaging, and biological markers of PD progression. © 2022 International Parkinson and Movement Disorder Society.